Kejadian Mortalitas Wanita dengan Kanker Payudara Berdasarkan Indeks Massa Tubuh (BMI): Tinjauan Naratif - Dahliana, Anita; Sukmantoro, Agung Anjar; Suryadinata, Rivan Virlando; Wahyuni, Titin; Aditya, Dwi Martha Nur (STIKES Yayasan RS.Dr.Soetomo, 2024)
Breast cancer is the most common cancer found in women of all types of cancer in the world. The relationship between body mass index and the death rate from breast cancer in women has drawn attention recently. This study sought to ascertain the relevance of the variation in death rates between women with breast cancer who had a normal body mass index (BMI) and those who had a BMI of ≥25. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) references were used to guide the systematic review process in this investigation. The Newcastle-Ottawa Scale for cohort design studies and the Robins-I test for single-arm experimental design studies were used to assess the quality of the articles. The data source consisted of 142 Pubmed publications published between 2016 and 2023. The analysis's findings revealed differences between the five publications that discussed the connection between obesity and breast cancer. The development of breast cancer is linked to an increase in leptin and estrogen, which is consistent with an increase in fat. It is concluded that individuals with a body mass index (BMI) of ≥ 25 had a poorer chance of surviving breast cancer than patients with a normal BMI.